A case report of a mammary gland type adenocarcinoma of the vulva in a patient with a concomitant breast cancer: a diagnostic challenge - Nobile, Ilenia; Tessitore, Antonia; Palumbo, Mario; Boccia, Dominga; Mignogna, Chiara; Bifulco, Giuseppe; Della Corte, Luigi (Frontiers in Oncology, 2026)
We describe the case of a 68‐year‐old woman who presented with a 4‐cm ulcerated lesion in the left paraclitoral area. Imaging revealed increased FDG uptake at the vulvar lesion and multiple skeletal sites but no suspicious inguinal lymphadenopathy, while breast imaging showed a 30‐mm BI‐RADS 5 lesion in the upper outer quadrant of the left breast. Core biopsies confirmed two distinct primaries: an invasive ductal carcinoma of the breast and an eccrine ductal‐type adenocarcinoma of the vulva arising from anogenital mammary‐like glands. A bone biopsy demonstrated metastatic breast carcinoma. The patient underwent radical anterior vulvectomy with bilateral sentinel lymph node biopsy; final pathology confirmed a well‐differentiated, adenocarcinoma of mammary‐gland type of the vulva (pT1bN0) with negative margins. Because of breast metastases, systemic therapy with ribociclib and letrozole was initiated but later discontinued owing to therapy‐related acute myeloid leukemia. At 9‐month follow‐up, no recurrence of the vulvar disease was observed. This report highlights one of the very few documented instances of synchronous mammary‐like vulvar carcinoma and breast carcinoma. It underscores the diagnostic complexity of the case and emphasizes the importance of an individualized, multidisciplinary approach tailored to tumor biology, staging, and patient comorbidities.